A Survey Study on the Factors Affecting Breastfeeding Self-Efficacy Among Postpartum Women in Mother–Infant Separation Wards - Cheng Cheng Si; Aimei Mao (SAGE Open Nursing)
Background Self-efficacy serves as a crucial predictor for successful breastfeeding. The standard practice in maternal wards is mother–baby rooming-in, which is believed to enhance breastfeeding rates post-delivery. However, in certain maternal wards, mother–baby separation continues to occur due to diverse factors. Objectives The objective of this study is to examine the self-efficacy levels of mothers in mother–infant separation wards and identify the factors that influence their self-efficacy. Methods A cross-sectional study was undertaken in 2022 at a hospital in Macau, involving 290 postpartum women in mother–infant separation wards. A self-designed questionnaire encompassing demographic details and breastfeeding information was utilized. Additionally, the Chinese version of the Breastfeeding Self-Efficacy Scale (BSES) and the Social Support Scale (SSRS) were employed. SPSS26.0 software was used to analyze the data. p  < .05 indicated statistically significant differences. Results The average breastfeeding self-efficacy score among the women was 96.03 ± 23.07, which accounted for 64% of the total score. The factors influencing breastfeeding self-efficacy were ranked based on their impact power as follows: previous experience of breastfeeding, intended length of breastfeeding, employment status, and the number of breastfeeding sessions during hospitalization after childbirth ( p  < .05). These four factors collectively explained 34.7% (R2 = 0.347) of the variations in breastfeeding self-efficacy scores. A weak but positive correlation was observed between postpartum women's breastfeeding self-efficacy and social support for the mothers ( r  = .341, p  < .001). Conclusion The breastfeeding self-efficacy scores of postpartum women were found to be at a moderate level. Mother–infant separation during the postpartum period has an impact on breastfeeding self-efficacy, but the impact can be managed. When developing programs to enhance postpartum mothers’ breastfeeding self-efficacy, it is important to consider their individual and social circumstances, as well as the advantages and disadvantages associated with mother–infant separation during the postpartum period.